A Simple Fluorescence Affinity Assay to Decipher Uranyl‐Binding to Native Proteins. (9th May 2022) - Laporte, Fanny; Chenavier, Yves; Botz, Alexandra; Gateau, Christelle; Lebrun, Colette; Hostachy, Sarah; Vidaud, Claude; Delangle, Pascale
Abstract: Determining the affinity of proteins for uranyl is key to understand the toxicity of this cation and to further develop decorporation strategies. However, usual techniques to achieve that goal often require specific equipment and expertise. Here, we propose a simple, efficient, fluorescence‐based method to assess the affinity of proteins and peptides for uranyl, at equilibrium and in buffered solution. We first designed and characterized an original uranyl‐binding fluorescent probe. We then built a reference scale for uranyl affinity in solution, relying on signal quenching of our fluorescent probe in presence of high‐affinity uranyl‐binding peptides. We finally validated our approach by re‐evaluating the uranyl‐binding affinity of four native proteins. We envision that this tool will facilitate the reliable and reproducible assessment of affinities of peptides and proteins for uranyl. Abstract : A fluorescent uranyl probe was designed and validated for the reliable determination of uranyl–protein affinities, at equilibrium and in biologically relevant conditions.